ARTICLE REVIEW: PROTEIN AND LIPID REQUIREMENTS OF MUD CRAB (Scylla spp.) - Wastu Ayu Diamahesa; Rangga Idris Affandi (Universitas Mataram, 2024)
This article discusses the nutritional requirements, particularly protein and lipid, in mud crabs (Scylla spp.). Mud crabs are one of the seafood types with a continuously increasing global demand. This literature review aims to provide an overview of the protein and lipid requirements in three mud crab species, namely Scylla paramamosain, Scylla olivacea, and Scylla serrata, which are the focus of aquaculture research. The research method involves comprehensive and systematic literature searches using predefined keywords. The findings indicate that protein and lipid requirements can vary depending on the growth phase, water temperature, and other environmental conditions. During the early growth phases, such as the larval and juvenile stages, mud crabs require higher protein levels to support rapid growth and optimal organism development. However, as they reach adulthood, protein requirements tend to decrease alongside metabolic changes and reproductive activity. Several studies have identified protein and lipid requirements for various mud crab species. The results show that optimal protein and lipid levels may vary depending on the species and growth stage of mud crabs. Therefore, this information is crucial for the development of suitable artificial feeds to effectively support the growth and health of mud crabs. In conclusion, this research provides important insights into the nutritional requirements of mud crabs and can serve as a guide for farmers to formulate feeds tailored to the daily needs of the crabs. Thus, this article makes a valuable contribution to the development of sustainable and efficient mud crab aquaculture industries.